Two Naturally Occurring Mutations on FVII Gene (S363I-W364C) Altering Intrinsic Catalytic Activity - Peyvandi, Flora; De Cristofaro, Raimondo; Akhavan, Sepideh; Carew, Josephine A.; Landolfi, Raffaele; Bauer, Kenneth A.; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 2002)
Factor VII (FVII) requires the cleavage of an internal peptide bond and the association with tissue factor (TF) to attain its fully active FVIIa conformation. This event alone leaves FVIIa in a zymogen-like state of relatively low specific activity. The TF-induced allosteric enhancement of FVIIa’s activity contributes to the procoagulant activity of the complex. We have characterized two naturally occurring mutations (S363I W364C) on FVII gene. Both homozygous patients for each mutation have a normal FVII:Ag level associated to an undetectable FVII coagulant activity. The patient carrying the allele 364C had a more severe hemorrhagic diathesis than the S363I mutant. To understand the mechanism of these deficiency, in vitro expression analysis with further biochemical characterization of recombinant proteins of both mutants FVII-363I, FVII-364C and wild type (WTFVII) FVII constructs were done. The results recapitulated the patients’ plasma data with normal Ag level and no detectable coagulant activity. The D-F-Pip-R-pNA and CH3SO2-D-CHA-A-But-R chromogenic substrates were used to evaluate the amidolytic activity of WT and mutant FVII in presence and absence of recombinant tissue factor (rTF). Binding of FVII to rTF by a solid phase binding assay was done using recombinant human rTF. The results of amidolytic assays showed that rTF enhances 28 fold the value of the specificity of constant (kcat/Km) in WT but no activity was detectable in either mutant constructs under any condition. The equilibrium dissociation constant of rTF-FVIIa interaction showed Kd equal to 4.4 ± 0.2nM, 4.9 ± 0.5nM and 6 ± 0.9 of WT, 363I and 364C FVII forms, respectively. The Kd values of the non activated forms were equal to 24.7 ± 3.3, 24.4 ± 3.1 and 20.6 ± 4nM, respectively. These data demonstrate that, compared to the WT form, FVII-363I and FVII-364C have no significant affinity change for TF and that the detrimental effect of these two mutations is attributable to the loss of an efficient catalytic machinery in the FVII molecule causing a severe deficiency of coagulant activities.
Keywords: Factor VII; extrinsic coagulation; tissue factor